TCH-030 PET/CT Imaging with [11C]Choline as a Radiopharmaceutical For the Detection of Recurrent Prostate Cancer: A Reliable Production Method and Quality Control. (12th March 2013) - Riondato, M; Democrito, A; Bagnara, MC; Massollo, M; Sambuceti, GM
Abstract : Background: PET/CT Imaging with the radiopharmaceutical [11C]-choline has become a useful tool in the detection of prostate cancer, mainly used in the assessment of treated patients presenting rising PSA and negative response after conventional imaging procedures. Tracer uptake on tumoral tissues is correlated to an increased synthesis of membrane substrates: [11C]-choline is trapped by phosphorylation taking part on phosphatidylcholine turnover. The sensitivity of this diagnostic method (almost 100%) is greater than CT or PET-[18F]FDG implying the superiority of the PET-choline procedure. PET-choline was first investigated in the late 1990s although no specific monographs are included in main Pharmacopoeias. The use of this powerful tracer is now based on Clinical Trials but, on September 2012, the FDA approved the production and use of 'Choline C11 Injection' to help the detection of recurrent prostate cancer. Purpose: :To define the key role the pharmacist plays in the preparation of [11C]-choline IMPD for Clinical Trials, presenting the tracer production in the details. Quality Control for characterising the final product and releasing it as 'solutio iniectabilis' are also described. Materials and Methods: cyclotron (Eclipse, Siemens) Automatized synthesiser (ModularLab, Eckert Ziegler) GMP grade reagents and disposables [11C]labelling based on 'wet' methylation chemistry Results: [11C]carbon dioxide (50 GBq) was produced by cyclotron and delivered to the synthesiser placed in our radiopharmacy. Carbon dioxide was first reduced to methyl iodide, then dimethyl-aminoethanol was [11C]-methylated. Finally the product was purified and filtered obtaining 15 GBq of sterilised [11C]-choline (16 min total time and 30% yield). Radiochemical purity was higher than 98% and other CQs were performed in accordance with EPh [18F]FDG monograph. Conclusions: Due to the short half-life decay (20 min) [11C]-choline production must be performed in PET facilities with on-site cyclotron and radiopharmacy. We presented a reliable and safe method for producing [11C]-choline for 3–4 patients' PET scans. No conflict of interest.